2017
DOI: 10.1021/acs.jafc.6b05465
|View full text |Cite
|
Sign up to set email alerts
|

Octacosanol Attenuates Inflammation in Both RAW264.7 Macrophages and a Mouse Model of Colitis

Abstract: Octacosanol has multiple biological functions. In this study, the anti-inflammatory effect and molecular mechanism of octacosanol were evaluated by using dextran sulfate sodium (DSS)-induced ulcerative colitis model in mice and lipopolysaccharide (LPS)-stimulated mouse macrophage RAW264.7 cells. The colitis mouse model was induced by 3.0% DSS in 8-week ICR mice and octacosanol orally administered with 100 mg/kg/day. The results showed that octacosanol significantly improved the health status of mice and reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
94
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(100 citation statements)
references
References 47 publications
5
94
0
Order By: Relevance
“…Consistent with the nuclear translocation data, luciferase reporter assays found that δ-tocotrienol significantly inhibited NF-κB and AP-1 activities in a dose-dependent manner, as shown in Figure 7 A,B. MAPKs are found to be close with AP-1 and NF-κB activations [ 29 , 32 ]. Our results suggest that δ-tocotrienol may affect inflammatory cytokine expressions via MAPK/NF-κB and MAPK/AP-1 pathways.…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…Consistent with the nuclear translocation data, luciferase reporter assays found that δ-tocotrienol significantly inhibited NF-κB and AP-1 activities in a dose-dependent manner, as shown in Figure 7 A,B. MAPKs are found to be close with AP-1 and NF-κB activations [ 29 , 32 ]. Our results suggest that δ-tocotrienol may affect inflammatory cytokine expressions via MAPK/NF-κB and MAPK/AP-1 pathways.…”
Section: Resultssupporting
confidence: 73%
“…Total RNA from murine macrophages RAW 264.7 cells was extracted by the Trizol reagent kit (Transgen, Beijing, China) and was then reverse transcribed by using high-Capacity cDNA Reverse Transcription Kits (Applied Biosystems, Foster City, CA, USA). Consistent with Liu et al [ 28 ] and Guo et al [ 32 ], the relative mRNA expression levels of pro-inflammatory factors and iNOS were analyzed by real-time quantitative PCR (RT-qPCR). Cells were treated with δ-tocotrienol (5 μM, 10 μM, 20 μM) for 2 h followed by adding LPS (1 µg/mL) for 6 h. According to the manufacturer’s protocol, 1 μg total RNA extracted from RAW264.7 cells was used in reverse transcription reaction with the One Step RT-PCR kit (Gibco-BRL).…”
Section: Methodsmentioning
confidence: 95%
See 2 more Smart Citations
“…TrkB-PLC/IP3 pathway is mainly consisted of protein-tyrosine kinase receptor B (TrkB), phospholipase C (PLC) and inositol triphosphate (IP3). After the specific binding of brain-derived neurotrophic factor (BDNF) to TrkB, TrkB is phosphorylated to p-TrkB, which activates the signal transduction of PLC/IP3 in the downstream, thereby playing roles in the increase of intracellular Ca 2+ concentration, the enhancement of nerve-muscle excitation conduction, the promotion of cell mobility in the intestinal smooth muscle, and the promotion of intestinal motility [14][15][16][17][18][19]. At present, there is no research showing the regulatory mechanism of TrkB-PLC/IP3 pathway on colitis.…”
Section: Introductionmentioning
confidence: 99%